2007
DOI: 10.1073/pnas.0704380104
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state networks in the infant brain

Abstract: In the absence of any overt task performance, it has been shown that spontaneous, intrinsic brain activity is expressed as systemwide, resting-state networks in the adult brain. However, the route to adult patterns of resting-state activity through neuronal development in the human brain is currently unknown. Therefore, we used functional MRI to map patterns of resting-state activity in infants during sleep. We found five unique resting-states networks in the infant brain that encompassed the primary visual co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

52
532
6
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 621 publications
(591 citation statements)
references
References 50 publications
(59 reference statements)
52
532
6
1
Order By: Relevance
“…The first paper on the presence of functional brain networks in the neonatal brain was published in 2007 (Fransson et al, 2007) and a number of research groups have now committed to the challenging task of functional imaging in utero (Ferrazzi et al, 2014;Schöpf et al, 2012;Seshamani et al, 2014;Thomason et al, 2013). Collectively, these efforts have led to exciting insights into functional brain network architecture in the earliest phases following its emergence.…”
Section: Functional Network Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The first paper on the presence of functional brain networks in the neonatal brain was published in 2007 (Fransson et al, 2007) and a number of research groups have now committed to the challenging task of functional imaging in utero (Ferrazzi et al, 2014;Schöpf et al, 2012;Seshamani et al, 2014;Thomason et al, 2013). Collectively, these efforts have led to exciting insights into functional brain network architecture in the earliest phases following its emergence.…”
Section: Functional Network Developmentmentioning
confidence: 99%
“…Historically, much of what we know about the intricate processes of early brain development came from post mortem studies in human fetuses, neonates, and non-human primates (Flechsig, 1920;Goldman-Rakic, 1987;Innocenti and Price, 2005;Kostovic, 2002;LaMantia and Rakic, 1990). With the increasing availability of high-quality neuroimaging techniques, including anatomical sequences customized to the developing neonatal and fetal brain, diffusion weighted imaging (DWI) and functional MRI, as well as electrophysiology recordings including electroencephalography (EEG), it has now become feasible to study early human brain development in unprecedented detail in vivo Counsell et al, 2007;Fransson et al, 2007;Huppi et al, 1998;Maas et al, 2004;Omidvarnia et al, 2014;Partridge et al, 2004;Smyser et al, 2001; Thomason et al, 2013;Toulmin et al, 2015;van den Heuvel et al, 2014). These advances have led to exciting new insights into both healthy and atypical macroscale brain network development and have paved the way to bridge the gap between the brain's neurobiological architecture and its behavioral repertoire.…”
Section: Introductionmentioning
confidence: 99%
“…Many other studies have looked at functional network development in young infants [19,20,22,56]. Fransson et al, in particular, examined the resting-state functional network architecture of very young preterm infants (25 weeks mean gestational age) and found that only half of the number of resting-state sub-networks found in healthy adults were present at the preterm stage [20].…”
Section: Introductionmentioning
confidence: 99%
“…Fransson et al, in particular, examined the resting-state functional network architecture of very young preterm infants (25 weeks mean gestational age) and found that only half of the number of resting-state sub-networks found in healthy adults were present at the preterm stage [20]. Recently, van der Heuvel et al found that functional networks in preterm infants agreed well with the underlying anatomical structure [54].…”
Section: Introductionmentioning
confidence: 99%
“…These methods simultaneously decomposes group fMRI data into modes describing variations across space, time, and subjects. It has been demonstrated that these methods can provide useful representations of group fMRI data in resting-state studies (Damoiseaux et al 2006;Fransson et al 2007;Jafri et al 2008).…”
Section: Spatial Pattern Analysismentioning
confidence: 99%